2012
DOI: 10.1049/iet-cds.2012.0011
|View full text |Cite
|
Sign up to set email alerts
|

Low-power processor architecture exploration for online biomedical signal analysis

Abstract: In this study, the authors explore sequential and parallel processing architectures, utilising a custom ultra-low-power (ULP) processing core, to extend the lifetime of health monitoring systems, where slow biosignal events and highly parallel computations exist. To this end, a single-and a multi-core architecture are proposed and compared. The single-core architecture is composed of one ULP processing core, an instruction memory (IM) and a data memory (DM), while the multi-core architecture consists of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…power transitions, page transfers, core cycle counters, memory accesses, etc.). Power values obtained from post-placeand-route power analysis of various components (see details in Section 4.2.1) are afterwards used to annotate the simulator to compute the system-level power consumption [Dogan12b].…”
Section: Architecture-level Frameworkmentioning
confidence: 99%
“…power transitions, page transfers, core cycle counters, memory accesses, etc.). Power values obtained from post-placeand-route power analysis of various components (see details in Section 4.2.1) are afterwards used to annotate the simulator to compute the system-level power consumption [Dogan12b].…”
Section: Architecture-level Frameworkmentioning
confidence: 99%
“…In our sliding window implementation we applied a window of 2 minutes of sampled RR-intervals with 50% overlap between the windows. The system was mapped on a simulator configured with typical sensor node parameters [13,14] and the profiling results are depicted in Fig. 1(b).…”
Section: B Profiling and Limitations Of A Conventional Psa Systemmentioning
confidence: 99%
“…In order, to evaluate the energy savings and the distortions obtained by the proposed approximations we have mapped the conventional and modified PSA system (with N=512 FFT) on a single RISC processor simulator configured with typical, available sensor node characteristics [13,14]. In particular, we are simulating a typical single-core sensor node that is accompanied with a 64KB SRAM.…”
Section: Energy Quality Trade-offs Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel computing using multiple cores can alleviate this issue, provided that applications can be parallelized. To this end, in [3] near threshold ultra-low-power (ULP) multi-and single-core architectures are compared in terms of power and performance ability for several multi-channel biosignal processing applications. It has been shown that the multi-core approach achieves better energy efficiency compared to the single-core approach for medium and high workloads [3].…”
Section: Introduction and Related Workmentioning
confidence: 99%